Terms of Efficiency Peer Pressure or How to Respect the Standards in Social Organizations - Masclet , David (Studia Oeconomica Posnaniensia, 2026)
The purpose of this paper is to investigate the conditions under which peer pressure helps in deterring the free riding problem. The comparison of situations with and without peer pressure indicates that under certain conditions peer pressure may solve the well-known free riding problem. However there are several limitations to peer pressure including (1) the fact that peer monitoring is costly when production and monitoring efforts are substituted; (2) the threat of sanctions is not credible when sanctions are costly to implement. Nevertheless, strongly inequality averse individuals may still be encouraged to punish free riders despite the existence of a cost to - in the punishment of free riders.